Analisis Kuantitatif Informed Consent pada Tindakan Sectio Caesarea di Rumah Sakit Patria IKKT Jakarta Barat - Nurmayantih; Nanda Aula Rumana; Daniel Happy Putra; Puteri Fannya (Yayasan Literasi Sains Indonesia, 2022)
Informed Consent is the consent given by the patient or his family on the basis of an explanation of the medical/surgical action to be performed on the patient and this informed consent must be complete. In performing sectio caesarea, the informed consent sheet is not filled in, so any action taken can be categorized as malpractice. Researchers found that there were still many incomplete informed consent forms, especially informed consent for sectio caesarea surgery. The purpose of the study was to determine the quantitative analysis of informed consent for sectio caesarea at the Patria IKKT Hospital for the period March - April 2021 based on 4 components, namely knowing the completeness of patient identification, author authentication, and completeness of important reports, good records. This type of research is quantitative with descriptive design and data collection techniques are observation, checklist. This research was conducted using systematic random sampling method. The results of the study of 90 informed consent sheets for sectio caesarea, the average completeness of the patient identification filling component was 100%, the important component of filling out the report was an average of 86%, the author's authentication component had an average of 97.9%, the component of filling out good notes had an average of 97.9%. the average completeness is 93.7%. The results of the recapitulation of quantitative analysis have an average completeness of 94.4%.